Potential co-infection of influenza A, influenza B, respiratory syncytial virus, and Chlamydia pneumoniae: a case report with literature review - Feng, Yuanyuan; Wen, Shengzhu; Xue, Song; Hou, Meigui; Jin, Ying (Frontiers in Medicine, 2024)
The occurrence of a co-infection involving four distinct respiratory pathogens could be underestimated. Here, we report the case of a 72-year-old woman who presented to a community hospital with a cough productive of sputum as her main clinical manifestation. Antibody detection of common respiratory pathogens revealed potential co-infection with influenza A, influenza B, respiratory syncytial virus, and Chlamydia pneumoniae. We treated her with 75 mg oseltamivir phosphate administered orally twice daily for 5 days, 0.5 g azithromycin administered orally for 5 days, and 0.3 g acetylcysteine aerosol inhaled twice daily for 3 days. The patient showed a favorable outcome on the eighth day after early diagnosis and treatment. Since co-infection with these four pathogens is rare, we performed an extensive PubMed search of similar cases and carried out a systematic review to analyze the epidemiology, clinical manifestations, transmission route, susceptible population, and outcomes of these four different pathogens. Our report highlights the importance for general practitioners to be vigilant about the possibility of mixed infections when a patient presents with respiratory symptoms. Although these symptoms may be mild, early diagnosis and timely treatment could improve outcomes. Additionally, further research is warranted to explore the potential influence of SARS-CoV-2 infection on the co-occurrence of multiple respiratory pathogens.